2013
DOI: 10.24127/pj.v2i2.690
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Reading Comprehension Between Students of Junior High Schools in City and Rural Area

Abstract: This study is aimed to: (1) find out the differences on reading comprehension between students of junior high school in city and rural area, (2) to find out factors that causes differences on reading comprehension between students in city and rural area. This resarch was carried out in SMPN 1 Serang, SMPN 1 Cilegon, SMPN 1 Picung and SMPN 1 Banjarsari. The method used was quantitative method in the form of comparative study. The writer used Ex Post Facto Design in this research. The population of the research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…In line with this, many researchers such as Keskin [46], Yıldız [47], Kerubo [29], and Hijazi [48] disclosed that there was a statistically significant relationship between students' reading comprehension and their achievement in English since reading comprehension positively affects students' achievement. Besides, Sholihah [49] specifically highlights that urban students are interested much in reading the text related to academics like science and new technologies, for example, texts related to computers, Internet, and mobile phones, whereas the students of rural areas have tended to receive a text that is derived from the teacher only. It can be inferred that the differences in reading exposure and practice have brought a significant difference in the reading scores of the students in the two settings.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, many researchers such as Keskin [46], Yıldız [47], Kerubo [29], and Hijazi [48] disclosed that there was a statistically significant relationship between students' reading comprehension and their achievement in English since reading comprehension positively affects students' achievement. Besides, Sholihah [49] specifically highlights that urban students are interested much in reading the text related to academics like science and new technologies, for example, texts related to computers, Internet, and mobile phones, whereas the students of rural areas have tended to receive a text that is derived from the teacher only. It can be inferred that the differences in reading exposure and practice have brought a significant difference in the reading scores of the students in the two settings.…”
Section: Discussionmentioning
confidence: 99%
“…She found out that the students' low comprehension was due to the students' limited vocabulary and complex text structures. Next study proposed about reading competency beyond texts, namely reading habits and confidence (Fazal et al, 2012;Sholihah, 2013). These studies observed the students then concluded that bad reading habit lowered the students' reading motivation and selfconfidence in reading.…”
Section: Introductionmentioning
confidence: 99%